2012
DOI: 10.1097/anc.0b013e31826853fe
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental Noise and Infant Position on Cerebral Oxygenation

Abstract: Purpose To assess how different infant positions and peak sound levels effected cerebral oxygen saturation over time. Subjects Twenty-four premature infants who were born less than 32 weeks gestational age without congenital cardiac, neurological, and gastrointestinal anomalies. Design Repeated measures design with the first observation between 2 and 48 hours of life; once again between 49 and 96 hours of life; on Day of Life 7; and every 7 days thereafter until discharge home, transfer to another hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
1
23
0
2
Order By: Relevance
“…Two studies included infants with a postnatal age ≤72 h [30,33]. Postnatal age in the other three studies varied considerably within, as well as between studies, ranging from 1 h to 3 weeks [31,32,34]. The designs of the included studies were predominantly prospective observational; there was 1 RCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies included infants with a postnatal age ≤72 h [30,33]. Postnatal age in the other three studies varied considerably within, as well as between studies, ranging from 1 h to 3 weeks [31,32,34]. The designs of the included studies were predominantly prospective observational; there was 1 RCT.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full-text articles, 24 of these 29 articles did not meet the inclusion criteria and were therefore excluded (12 reports on children/infants with a GA >30 weeks, 7 described no relevant outcome parameters, 1 letter to the editor, 1 case report, and 3 poster abstracts). Finally, 5 studies were included in this systematic review [30,31,32,33,34]. Figure 1 provides a flowchart of the study selection.…”
Section: Resultsmentioning
confidence: 99%
“…24 Ayrıca, bu bebeklere pozisyon verirken başının orta hatta tutulması venöz dönüşü kolaylaştırarak kafa içi kanama olasılığını azalt-maktadır. 26,27 Bebek, başı orta hatta, gövdesi fleksiyonda olacağı, kendini rahatlatabileceği ve yatış şek-lini değiştirebileceği pozisyonda yatırılmalıdır. Zamanında doğan bebeklerle karşılaştırıldığında prematüre bebekler daha hipotonik olduğundan, fleksiyon postürünü korumaları için desteklenmeleri daha önemlidir.…”
Section: Prematüre Bebeklerde Pozi̇syonun Etki̇leri̇unclassified
“…However, there is currently no consensus on which position is suitable for very preterm neonates in the early days of life. For example, some studies evaluating alterations of cerebral oxygenation with head positioning and/or bed tilting on non-mechanically ventilated infants (24)(25)(26), or others assessing the effects of supine or prone positioning on ventilated and spontaneous breathing of premature newborns have reported that cerebral oxygenation was not significantly affected by changes in positioning (24,27).…”
Section: Introductionmentioning
confidence: 99%